2021
DOI: 10.1029/2020gl091994
|View full text |Cite
|
Sign up to set email alerts
|

The Synoptic to Decadal Variability in the Winter Surface Wind Speed Over China by the Weather Regime View

Abstract: The observed surface wind speed (SWS) has declined over the past 4 decades over China, which have has been examined from a climatological perspective. However, the SWS is highly variable and is dependent on the weather regime (WR). This study investigates the variability of winter SWS under six typical WRs and assesses the variability at the synoptic to decadal time scales. Our results reveal that the WRs impose important impacts on the spatial pattern and inter‐annual variability of SWS over China. The Siberi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These findings suggest that in recent years, the global wind speed also has had a weak mean state and variability. Many previous studies have suggested that large‐scale circulations and urbanization are important factors to the observed wind stilling 40,68–70 . The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia 68 .…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings suggest that in recent years, the global wind speed also has had a weak mean state and variability. Many previous studies have suggested that large‐scale circulations and urbanization are important factors to the observed wind stilling 40,68–70 . The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia 68 .…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Many previous studies have suggested that large-scale circulations and urbanization are important factors to the observed wind stilling. 40,[68][69][70] The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia. 68 As for urbanization, it ignored in the regional NWS decline, but it does not play a dominant role.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large ensemble models may play a good role in investigating this issue (Li et al., 2021). (c) The dominant physical mechanisms behind the projections across the subregions remain different and unclear, including the effects of temperature gradient, surface friction, land use, upper‐level jet stream, and boundary layer processes (Pryor et al., 2012; Shen et al., 2023; Wu et al., 2018; Zha et al., 2021). (d) The scarcity of daily‐resolution situ stations limits our ability to use observations to evaluate CMIP6 simulations (Wu et al., 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Numerous physical mechanisms, such as asymmetrical latitudinal warming (Karnauskas et al., 2018), changes in surface roughness (Myneni et al., 1997), subtropical jet (Shen et al., 2023) and land‐sea thermal gradient (Karnauskas et al., 2018), have been proposed in previous studies to explain the changes in WPD. Nevertheless, separating and quantifying the impact of these mechanisms on WPD remains a challenge due to the diverse factors influencing wind speed at varying scales.…”
Section: Discussionmentioning
confidence: 99%